Generations in Estonia: Contemporary Perspectives on Turbulent Times - Nugin, Raili (Approaches to Culture Theory, 2016)
This book provides the international reader with the first study of different generations and intergenerational relations in Estonia. The chapters highlight generational patterns in the 20th and 21st centuries, with the volume as a whole taking an interdisciplinary approach. Sharing the idea that generations are dynamic, that their borders are blurred and change over time, and that their construction is interdependent, the authors have each chosen a specific perspective on and framework for generations. Several studies take an interest in how and by whom generations are constructed, and how generational identity has been perceived and reshaped over time. Others use generation as a concept or an analytical tool with which to investigate different social processes, or as a community of experience and carrier of memory. The volume suggests novel and diverse approaches to the definition of generation and the formation of generational consciousness, as well as to generational theory.